Market Entry Strategy of the Global Corporations on the Markets of China - Zhao, Ziye; Pichanič, Mikuláš, 1942-; Staňková, Anna, 1951-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
With the rapid development of social and economic globalization, the process of world economic globalization has become an irreversible trend. In the process of globalization, multinational companies are the most important carriers. However, the choice of market entry strategy is a key issue for the success of multinational corporations. Appropriate entry strategy will have a significant impact on the future management and business performance of enterprises. This will also bring huge convenience and profits to the enterprise. On the other hand, the speed and scope of Chinese economic growth make it unique. As one of the most attractive investment destinations for global investors, almost all the world's automobile manufacturing giants now have factories in China. Volkswagen Group is one of the earliest investors in China and the largest foreign automobile manufacturer, and its entry and development strategy has been very successful. This term paper will analyze which specific mode Volkswagen uses to enter the Chinese market, and analyze the reasons behind this choice in detail.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses